One CHiP to rule them all? Mechanistic insight into carfilzomib-induced lung injury with neutrophil extracellular trap formation following cellular immunotherapy - Julia Katharina Scholz; Lena Stabel; Nora Rebecca Schwingen; Jasmin Knopf; Anna-Sophie Flatt; Tobias Bäuerle; Stefan Krause; Heidi Waibel; Moritz Leppkes; K Martin Kortüm; Hermann Einsele; Andreas Mackensen; et al. (Haematologica)
Not available.